Windows of Faith and Freedom: A Muslim Woman's Narrative - Amani K Hamdan (Canadian Society for Studies in Education, 2012)
The West has typically constructed Muslim women as one of the most oppressed groups of women in the world. This article sheds light on a narrative inquiry into the experiences and perspectives of Fadwa, a young Muslim woman living in North America. Making use of deconstructionist and poststructuralist analytical lenses, Fadwa's stories are highlighted as an example of possible negotiations for gender construction in Arab Muslim societies. In addition, the impact of education in Canada on Fadwa's worldviews is explored and the struggles that Fadwa experienced as a result of living in different cultures are highlighted. It is hoped that Fadwa's stories will contribute to a more comprehensive understanding of issues relating to the lives of Muslim women.